PERTANGGUNGJAWABAN PIDANA PENYIDIK KPK YANG MELAKUKAN PELANGGARAN DALAM PENANGANAN KASUS TINDAK PIDANA KORUPSI - Mohamad Jamil (SOL JUSTICIA, 2019)
The author discusses the criminal responsibility of KPK investigators who commit violations in handling cases of corruption. In this case the author takes the issue of when the actions of KPK investigators can be categorized as criminal acts in the event of irregularities in the process of examining criminal acts of corruption, as well as the form of criminal acts and legal liability related to criminal acts carried out by KPK investigators when examining corruption. The purpose of the author to raise the topic of this problem is to analyze when the actions of KPK investigators can be categorized as criminal acts in the event of a deviation in the process of examining criminal acts of corruption. The type of research conducted by this author is normative research, because the author will conduct research by analyzing the applicable laws regarding the form of criminal acts that can be carried out by KPK investigators in handling cases of corruption. The results of the research conducted by this author are that in the current positive law Indonesia has been regulated about forms of crime that can be made possible by KPK investigators in handling cases of corruption in the form of Law No. 31 of 1999 concerning the eradication of criminal acts of corruption has been revised into Law number 20 of 2001 and also regulated in the KPK Law, namely Law number 30 of 2002.